Creencias y costumbres en el cuidado materno a menores de 3 años con fiebre, centro de salud Sarín, Huamachuco 2012" - Caipo Ruiz, Santos Nicanor (2013)
This research is a descriptive - cross sectional correlation was conducted with students of the nursing career (last year), with the objective of determining the relationship between the level of satisfaction on learning assessment and academic factors: weighted average, rather of origin, type of tuition, residence time of (the) students in the nursing career at the School of Nursing at the Universidad Nacional de Trujillo 2012. The conclusions were arrived were: 1. The level of satisfaction with the assessment is mostly rated as satisfactory (45.0%), 33.6% dissatisfied. It should be noted that 10% are not satisfied and 11.4% very satisfied. 2. The weighted average is half rated highest percentage (65%), 33.6% regular and only 1.4% is high. On the place of origin for 59.3% of Trujillo, Huamachuco el22.9% and 17.9% of Jequetepeque Valley. The type is regular Registration mostly (78.6%) and 21.4% special. In relation to the time spent in accordance with the provisions of the 78.6% and more than expected 21.4%. 3. There is a highly significant relationship between the level of satisfaction on learning assessment and academic factors: weighted average, place of origin, type of registration, residence time of (the) students in the nursing career.